Ladybugs and other beetles : [book author, Steven Otfinoski]. - Otfinoski, Steven; World Book, Inc. (Chicago : World Book, 2000)
Questions and answers explore the world of beetles, with an emphasis on ladybugs.
Includes index.
Keywords: Beetles -- Juvenile literature; Ladybugs -- Juvenile literature; Beetles -- Miscellanea; Ladybugs -- Miscellanea; Questions and answers